Comparison of Passive Chromatic Dispersion Compensation Techniques for Long Reach Dense WDM-PON System - Bobrovs, Vjaceslavs; Spolitis, Sandis; Gavars, Peteris; Ivanovs, Girts (Elektronika ir Elektrotechnika, 2012)
The maximum reach of the DWDM-PON system can be severely limited by chromatic dispersion (CD). This paper contains the investigation of long-reach high speed 16-channel DWDM-PON system with efficient CD pre-compensation and post-compensation methods. It is shown that CD compensation has a crucial role for guaranteed downstream optical link performance and maximum link length of high speed long-reach DWDM-PON system. The results show that usage of additional 7 km long dispersion compensating fiber (DCF) placed in central office (pre-compensation configuration) improves the DWDM-PON network reach by 19.3% (from 57 km up to 68 km), but if additional 2 km long DCF fiber is used in remote terminal (post-compensation configuration) link length can be extended up to 5.3% (from 57 km to 60 km). It was found that usage of fiber Bragg grating (FBG) in central office (pre-compensation configuration) improves network reach up to 26.3% (from 57 km up to 72 km), but using this FBG for CD post-compensation in remote terminal network reach can be improved by 15.8% or 9 km in length – from 57 km to 66 km. Basis on the results authors recommend to use FBG as the best solution for CD compensation in pre-compensation configuration (before SMF line) in future high speed long-reach DWDM-PON systems. DOI: http://dx.doi.org/10.5755/j01.eee.122.6.1112